2020
DOI: 10.1155/2020/7673937
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Off-Grid Performance of the Hybrid Photovoltaic/Diesel Energy System for a Peripheral Village

Abstract: Grid extension from the distribution network is being used to meet the demand for rural electricity all over the world. Due to the extra cost of extending electric lines to rural villages, it is not feasible as the installing and commissioning costs are directly related to several constraints such as distance from the main grid, the land location, utilities to be used, and the size of the approximate load. Consequently, it becomes a challenge to apply technoeconomic strategies for rural electrification. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…[ 32 ], a hybrid renewable energy feasibility for the supply of a large resort center located in Malaysia was evaluated with HOMER. Some other works in which the HOMER software has been used are those of Yimen et al [ 33 ] where the PV/Biogas was considered, Iskanderani et al [ 34 ] where the PV/Diesel/Battery was considered, Aberilla et al [ 35 ] where the PV/Wind system was designed and Djiela et al where PV/Diesel/Battery system was proposed [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 32 ], a hybrid renewable energy feasibility for the supply of a large resort center located in Malaysia was evaluated with HOMER. Some other works in which the HOMER software has been used are those of Yimen et al [ 33 ] where the PV/Biogas was considered, Iskanderani et al [ 34 ] where the PV/Diesel/Battery was considered, Aberilla et al [ 35 ] where the PV/Wind system was designed and Djiela et al where PV/Diesel/Battery system was proposed [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The optimisation is subject to several constraints. The first is the energy system power balance, shown in Equation (3).…”
Section: Esmentioning
confidence: 99%
“…In ref. [3], a PV and diesel generator system was studied for rural areas of Bangladesh. The study revealed that an optimal PV, diesel generator and battery system does not reduce overall energy cost.…”
Section: Introductionmentioning
confidence: 99%
“…Different tariffs (ToU and developed step-rate tariffs) and FITs are applied to schedule the efficiency of the grid and the price of electricity. Besides, many researchers have implemented for optimization problems different software tools such as HOMER and TRYNS [22,23].…”
Section: Soc<soc Maxmentioning
confidence: 99%